The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1590/s1413-70542009000600005
|View full text |Cite
|
Sign up to set email alerts
|

Crescimento e acúmulo de fósforo pela soja cultivada em sucessão a diferentes gramíneas forrageiras adubadas com super fosfato triplo e fosfato reativo de arad

Abstract: RESUMOConduziu-se este trablho, com o objetivo de avaliar o efeito do cultivo prévio de diferentes gramíneas forrageiras, adubadas com superfosfato triplo (SFT) e fosfato reativo de arad (FRA), sobre o crescimento, produção e acúmulo de P pela soja. Foram realizados dois experimentos, um em Cambissolo Háplico tb distrófico típico e o outro em Latossolo Vermelho distrófico típico textura muito argilosa. Para os dois experimentos, o delineamento experimental foi o inteiramente casualizado em esquema fatorial 4 x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…Moreover, some of the undissolved RRP might add to the extracted Ca-P, as evidenced by higher Ca-P in the 0-5 cm soil depth of plots. Similar results were obtained by Rodrigues et al (2009), which observed increases in Ca-P after RRP application. The effect of ruzigrass in reducing Ca-P, in soluble phosphate plots, is likely related to the utilization of this P fraction by the cover crop.…”
Section: Resultssupporting
confidence: 88%
“…Moreover, some of the undissolved RRP might add to the extracted Ca-P, as evidenced by higher Ca-P in the 0-5 cm soil depth of plots. Similar results were obtained by Rodrigues et al (2009), which observed increases in Ca-P after RRP application. The effect of ruzigrass in reducing Ca-P, in soluble phosphate plots, is likely related to the utilization of this P fraction by the cover crop.…”
Section: Resultssupporting
confidence: 88%
“…These data demonstrate that soluble P released by the soluble source was taken up and stored in ruzi grass tissues, and it was not released and mineralized in time to meet the next crop demand, ensuring a better response to the soluble source in the absence of the cover crop. Rodrigues et al (2009) also found that forages such as pearl millet, brachiarias, and sorghum immobilized P from TSP, decreasing its residual effect for soybeans; when grasses were fertilized with NRP, there was an increase in the residual effect, with better P use efficiency by the soybean crop grown following these cover crops.…”
Section: Resultsmentioning
confidence: 87%
“…Therefore, high levels of available P in soil did not result in a higher P accumulation in the plants when the crop had been directly fertilized with P. This shows that the P applied to the pasture preceding the soybean and available to the plant is used more efficiently than P fertilizer applied at soybean sowing. Rossi et al (1999) evaluated the residual effect of four P levels and four phosphorus sources applied to two pastures (Centrosema pubescens and Brachiaria decumbens) preceding rice cultivation: they also noted the residual effect of P coming from triple superphosphate applied to pasture. Considering the role of the root system of grasses in the solubilization of P by the exudation of organic acids (CORRÊA et al, 2004), Urochloa decumbens may have played a key role in the absorption efficiency of residual P and its subsequent release by mineralization of P held in DM (organic P).…”
Section: Fertilization In Pasturementioning
confidence: 99%
“…Another strategy is to apply all or part of the annual crop's fertilization to the preceding crop, which is usually a green manure in non-tilled pasture or crop-livestock systems . Francisco et al (2007) and Rodrigues et al (2009) reported that early P fertilization of wiregrass [Eleusine coracana (L.) Gaertn. ], produced more plant biomass and an accumulation of P which did not affect soybean grain yield.…”
Section: Introductionmentioning
confidence: 99%